2022 National Standards for Diabetes Self-Management Education and Support. Issue 1 (February 2022) - Davis, Jody; Fischl, Amy Hess; Beck, Joni; Browning, Lillian; Carter, Amy; Condon, Jo Ellen; Dennison, Michelle; Francis, Terri; Hughes, Peter J.; Jaime, Stephen; Lau, Ka Hei Karen; McArthur, Teresa; et al.
Purpose: The National Standards for Diabetes Self-Management Education and Support (DSMES) provide guidance and evidence-based, quality practice for all DSMES services. Due to the dynamic nature of health care and diabetes research, the National Standards are reviewed and revised approximately every 5 years by key stakeholders and experts within the diabetes care and education community. For each revision, the Task Force is charged with reviewing the current National Standards for appropriateness, relevance, and scientific basis and making updates based on current evidence and expert consensus. In 2021, the group was tasked with reducing administrative burden related to DSMES implementation across diverse care settings. Conclusion: The evidence supporting the 2022 National Standards clearly identifies the need to provide person-centered services that embrace cultural differences, social determinants of health, and the ever-increasing technological engagement platforms and systems. Payers are invited to review the National Standards as a tool to inform and modernize DSMES reimbursement requirements and to align with the evolving needs of people with diabetes (PWD) and physicians/other qualified health care professionals. The American Diabetes Association and the Association of Diabetes Care & Education Specialists strongly advocate for health equity to ensure all PWD have access to this critical service proven to improve outcomes both related to and beyond diabetes. The 2022 National Standards update is meant to be a universal document that is easy to understand and can be implemented by the entire health care community. DSMES teams in collaboration with primary care have been shown to be the most effective approach to overcome therapeutic inertia.